Synthesis of WO3@ZnWO4@ZnO-ZnO hierarchical nanocactus arrays for efficient photoelectrochemical water splitting. (November 2017) - Yuan, Kaiping; Cao, Qi; Li, Xinyu; Chen, Hong-Yan; Deng, Yonghui; Wang, Yuan-Yuan; Luo, Wei; Lu, Hong-Liang; Zhang, David Wei
Abstract: Hierarchical heterostructures with large surface areas and multiple interfaces as photoanode materials, are holding great promise for photoelectrochemical (PEC) water splitting toward efficient solar energy utilization. In this work, the cactus-like WO3 @ZnWO4 @ZnO-ZnO ( i.e. W@WZ@Z-Z) arrays compromising the first-order W@WZ@Z core-shell nanosheets and the second-order ZnO nanosheets, have been fabricated by combining atomic layer deposition (ALD) technique and hydrothermal process. The modification of ZnO nanosheets on the surface of WO3 and the simultaneous formation of ZnWO4 in-between buffer layer have endowed the photoanode a drastic enhancement in both ultraviolet light absorption and charge separation via the favorable band alignment at the WO3 -ZnWO4 -ZnO interfaces. Particularly, the W@WZ@Z-Z nanocactus (NC) array photoanode with a 30 nm ZnO layer on WO3 precisely controlled by ALD, exhibited around 3.8 times higher photocurrent density ( 1.57 mA/cm 2 ) at 1.23 V vs. RHE than pristine WO3 photoanode ( 0.41 mA/cm 2 ), with little loss after long-term continuous illumination as well. Overall, the novel combination of WO3 with ZnO and the ZnWO4 buffer layer, and construction of hierarchical heterostructures, along with the resulted improvement in light absorption and charge separation which have been confirmed by spectroscopic characterizations and finite-difference time-domain simulation, suggest many exciting opportunities for further development of high-performance PEC devices for solar energy conversion. Graphical abstract: Highlights: A large-scale array of 3D heterostructured hierarchical WO3 @ZnWO4 @ZnO-ZnO nanoacatus was formed. The nanocactus array shows an improvement of light absorption and the transfer of charge carriers. The proposed photoanode has an efficent PEC performance.